1993
DOI: 10.1128/jb.175.4.1087-1094.1993
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol kinase of Escherichia coli is activated by interaction with the glycerol facilitator

Abstract: Glycerol transport is commonly cited as the only example of facilitated diffusion across the Escherichia coli cytoplasmic membrane. Two proteins, the glycerol facilitator and glycerol kinase, are involved in the entry of external glycerol into cellular metabolism. The glycerol facilitator is thought to act as a carrier or to form a selective pore in the cytoplasmic membrane, whereas the kinase traps the glycerol inside the cell as sn-glycerol-3-phosphate. We found that the kinetics of glycerol uptake in a faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
0
3

Year Published

1993
1993
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 36 publications
6
64
0
3
Order By: Relevance
“…However, studies of the solubilized glycerol channel GlpF from Escherichia coli (Braun et al, 2000) revealed a square-shaped particle similar in size and mass to those found for aquaporins (Hasler et al, 1998;Ringler et al, 1999;Walz et al, 1994). A tetrameric structure of GlpF also supports the model of direct interaction of the tetrameric glycerol kinase from E. coli with GlpF (Voegele et al, 1993).…”
Section: Introductionsupporting
confidence: 54%
“…However, studies of the solubilized glycerol channel GlpF from Escherichia coli (Braun et al, 2000) revealed a square-shaped particle similar in size and mass to those found for aquaporins (Hasler et al, 1998;Ringler et al, 1999;Walz et al, 1994). A tetrameric structure of GlpF also supports the model of direct interaction of the tetrameric glycerol kinase from E. coli with GlpF (Voegele et al, 1993).…”
Section: Introductionsupporting
confidence: 54%
“…Furthermore GUP1 and GUP2 have recently been proposed to be involved in active transport of glycerol in yeasts (13). In contrast, the physiologically relevant role of GlpF from Escherichia coli, the closest bacterial homolog of Fps1p with 30.5% identity, is likely to be import of glycerol for catabolism (14,15).…”
Section: Major Intrinsic Protein (Mip)mentioning
confidence: 99%
“…The GIpF protein has been described as a cytoplasmic membrane 'channel' which also facilitates the passage of polyhydric alcohols such as ribitol and erythritol as well as unrelated small molecules like urea and glycine [31]. The postulated facilitator function of GIpF has recently been questioned, because passive diffusion of glycerol across the cytoplasmic membrane is not rate-limiting for phosphorylation in a GlpF-mutant [32]. On the basis of these observations it has been suggested that GIpF acts as an activator of glycerol kinase (GlpK), although the role of GIpF in facilitating transport has not been refuted.…”
Section: Ii-b Electroneutral Solute Uniport (Fig 1-1)mentioning
confidence: 99%